The Menstrual Cycle and Risk of Breast Cancer: A Review - Olsson, Håkan Lars; Olsson, Mona Landin (Frontiers in Oncology, 2020)
Cyclic hormonal stimulation of the breast tissue plays a significant role in is of outmost importance for breast carcinogenesis . So farCurrent risk factor models have not incorporated do not include direct measures of cycle characteristics but althoughused the effects of possible surrogates of cycle activity such as age at menarche and, age at menopause, parity, and nursing time have been investigated. Future risk models should also should include also menstrual cycle length, regularity, and number of cycles before first full- term pregnancy, and life -time number of cycles. New risk factor models for pre- and postmenopausal breast cancer are proposed here. Furthermore, Tthere is also a need for more long- term, prospective studies on investigating menstrual cycle characteristics as data currently availablenow mainly are refer primarily to retrospective data and collected at one time- point only.